Cerebral Venous Thrombosis with Papilloedema Secondary to Skull Base Plasmacytoma. (3rd September 2017) - MacIntosh, Peter W.; Lin, Amy Y.; Kim, Jin Suh; Testai, Fernando D.; Moss, Heather E.
ABSTRACT: A 60-year-old woman with history of multiple myeloma was in remission after stem cell transplant 6 years prior. She was undergoing work-up for headaches that were thought to be secondary to a right mastoiditis seen on magnetic resonance imaging (MRI). On routine eye exam, papilloedema was noted. A lumbar puncture was performed, with elevated opening pressure with normal constituents. She was an atypical age for idiopathic intracranial hypertension, and her mastoiditis raised concern for secondary cerebral venous sinus thrombosis. Magnetic resonance venography (MRV) was performed showing poor flow in the right sigmoid sinus, and computed tomography venography (CTV) showed lack of contrast enhancement distal to the right sigmoid sinus, consistent with occlusion. There was also an enhancing mass inferior to the right occipital bone. Biopsy confirmed recurrent plasma cell myeloma. She was treated with chemotherapy, radiation, and warfarin for presumed cerebral venous sinus thrombosis.